The Effect Of Aggregate Types On The Performance Of Asphalt Mixture Incorporating Silane Additive Zycotherm - Nathan, Pavanithan (Universiti Sains Malaysia, 2017)
The bond within asphalt mixture constituents fails in the presence of different mechanism interacting at the interface which results in various forms of distress initiated from the aggregate-asphalt binder surface and cohesive failure within the asphalt binder. It shortens the service life of asphalt mixtures, resulting in failures such as cracking, rutting and potholes. This study concentrates on the aggregates and the effects of adding silane additive to the asphaltic mixture. Mixing and compaction temperatures of 160 ℃ and 150 ℃ respectively was adopted to produce control mixture hot mix asphalt (HMA). While, asphalt mixtures incorporating Zycotherm was mixed and compacted at 145 °C and 125 °C respectively. The serviceability of asphaltic mixture was measured using Workability Index (WI), Coatability Index (CI) and Compaction Energy Index (CEI). Whereas the moisture damage is evaluated by comparing the Accelerated Lab Vacuum Saturator (ALVS) conditioned samples with the dry controlled samples using Indirect Tensile Strength Test (ITS) and Cantabro test. Leutner Shear test was used to test the bonding between aggregates and binder in asphaltic concrete. Based on the test results, it was found that granite is having a better performance in terms its service characteristics at controlled hot mixed asphalt (HMA) whereas limestone is performing well at lower mixing temperature. From the Coatability Index, granite has better binder coating as compared to limestone. The asphalt mixture performance generally favours to the granite at HMA temperature. However, the Zycotherm added asphalt mixture gives a better resistance to moisture and disintegration. In term of the intra-bonding of binder and aggregates, the granite at HMA temperature has the stronger bonds.